Effect of Slope and Distance from Oil Palm Stands on Soil Water Content - Siringoringo, Naomi Yulia; Gusmara, Herry; Prawito, Priyono; Prasetyo, Prasetyo; Utami, Kartika (TERRA : Journal of Land Restoration, 2023)
This study aims to study the effect of land slope and distance from the main crops on soil water content at the end of the rainy season. The research location is located at position 3°41'51.8"S - 102°18'58.0"East in Talang Tengah I Village, Pondok Kubang District, Central Bengkulu. The research was conducted in February - April 2021. Soil analysis was done at the Soil Laboratory, University of Bengkulu. The study used a completely randomized block design with two factors. The first factor is the slope of 0-3% and 30%. The second factor is the distance of the cutting slope from the main oil palm tree, namely 1.5; 2.0; 2.5; 3.0; 3.5; and 4.0 m. Data were analyzed using ANAVA and LSD at 5% level. The results showed that the slope of the land and the distance between the slopes had a significant effect on the soil water content. The soil water content in both gravimetric and volumetric methods on slopes of 0-3% is higher than on slopes > 30%. The water content at a distance of 1.5 to 3 m from the tree of oil palm is lower than at a distance of 3.5 – 4.0 m.